Krukenberg tumor and pregnancy - Albújar, Pedro (2015)
We present the case of a 26 years old woman with a 21 weeks pregnancy who had a secondary ovarian cáncer to a primary gastric cáncer (Krukenberg tumor). We review the clínical features associated to a Krukenberg tumor with pregnancy and epidemiology, laboratory findings, pathology, further therapeutic attitude with the tumor and pregnancy, gloomy prognosis.